Why is adolescent drinking declining? A systematic review and narrative synthesis. (3rd July 2020) - Vashishtha, Rakhi; Livingston, Michael; Pennay, Amy; Dietze, Paul; MacLean, Sarah; Holmes, John; Herring, Rachel; Caluzzi, Gabriel; Lubman, Dan I.
Abstract: Background: Adolescent drinking has declined across many developed countries from the turn of the century. The aim of this review is to explore existing evidence examining possible reasons for this decline. Methods: We conducted systematic searches across five databases: Medline, PsycINFO, CINAHL, Informit Health and Scopus. Studies were included if association between declining alcohol consumption and potential explanatory factors were measured over time. Narrative synthesis was undertaken due to substantial methodological heterogeneity in these studies. Results: 17 studies met the inclusion criteria. Five studies found moderate evidence for changes in parental practices as a potential cause for the decline. Five studies that examined whether alcohol policy changes influenced the decline found weak evidence of association. Three studies explored whether alcohol use has been substituted by illicit substances but no evidence was found. Two studies examined the effect of a weaker economy; both identified increase in adolescent alcohol use during times of economic crisis. One study indicated that changes in exposure to alcohol advertising were positively associated with the decline and another examined the role of immigration of non-drinking populations but found no evidence of association. One study tested participation in organised sports and party lifestyle as a potential cause but did not use robust analytical methods and therefore did not provide strong evidence of association for the decline. Conclusions: The most robust and consistent evidence was identified for shifts in parental practices. Further research is required using robust analytical methods such as ARIMA modelling techniques and utilising cross-national data.